(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Translation is a general term that refers to the expression of thoughts and ideas from one language to another, so the content of the translation must correspond to the original text. In addition, translating from one language to another facilitates cross-cultural communication, which is necessary in today’s society, that is, formal equivalence, translation and dynamic equivalence must pay special attention to the compatibility of the translation with the receptor language and culture. Dynamic equivalent translation conveys the message of the original text, so the response of people who read or heard the translated message is the same as the response of people who read or heard the original text